2.5 million hectares and one sustainable goal. Issue 2 (2014) - Daniel A. Moscovici
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to investigate historical environmental destruction and subsequent land use policies enacted over the last 400 years in the Adirondacks Park & Preserve – America's largest park and preserve in the lower 48 states. Design/methodology/approach – The paper includes a historical analysis using an extensive literature review. The historical analysis is divided into four distinct waves of time analyzing the specific environmental destruction and the policies enacted. They closely mimic century waves: 1700s, 1800s, 1900s, and the present 2000s. Findings – Findings indicate that each of the major policy or land use instruments applied to the Adirondack region were appropriate at the time, however, were retroactive approaches to stem widespread environmental devastation. These strong measures still impact the region today, impairing the 2.5 million ha and the ability to ensure a sustainable future of environmental protection, economic prosperity, and societal well‐being. The conservation easement as a tool can proactively return the region to a sustainable balance. Originality/value – While there have been studies analyzing the historical importance and others highlighting the political uniqueness of the Adirondacks, this paper fills the gap in reframing the history and policies in a sustainable planning paradigm. Exposing retroactive responses when the environment was on the brink of destruction, the paper suggests a proactive approach using the conservation easement. Here, sustainability can be achieved through partnership between government, non‐profit, and private business. This collaboration can build on one of the best regional planning models in the nation and ensure a balance between environment, economy, and society for more than one century wave.